Ta'tsir Musyahadah Qishshah An-Nabi Muhammad SAW Ala Itqan Al-Mufradat Al-Arabiyah Li At-Talibat Ma'had Safinatussalamah Aceh Singkil - Nanda Tsabita Herba; Harun Al-Rasyid (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2025)
Vocabulary mastery is a crucial component in the process of learning Arabic, especially in Islamic boarding schools (pesantren) where the language serves as the primary medium for understanding Islamic teachings through classical literature. Unfortunately, many female students (santriwati) lack motivation in memorizing vocabulary (mufradat), which poses a challenge in the learning process. This study aims to determine whether watching stories of the prophets can positively influence the improvement of Arabic vocabulary mastery among santriwati at Pondok Pesantren Safinatussalamah, Aceh Singkil. The research employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. A total of 25 santriwati were selected as the sample using purposive sampling technique. The research instrument was a multiple-choice test administered before and after the treatment (watching prophetic story films). The collected data were analyzed using t-test and simple linear regression. The results showed that watching stories of the prophets significantly improved the Arabic vocabulary mastery of the santriwati. These findings indicate that audiovisual media can be an effective alternative strategy to enhance Arabic language learning in pesantren environments.